Prevalence, Awareness, Treatment, Control, and the Associated Factors of Diabetes in an Iranian Kurdish Population. (3rd September 2019) - Safari-Faramani, Roya; Rajati, Fatemeh; Tavakol, Kamran; Hamzeh, Behrooz; Pasdar, Yahya; Moradinazar, Mehdi; Najafi, Farid
Abstract : Aims . This study is aimed at estimating the prevalence, awareness, treatment, and glycemic control of diabetes mellitus (DM) and its associated factors in an Iranian Kurdish population. Methods . Baseline data of the Ravansar Non-communicable Disease (RaNCD) cohort study, consisting of adults aged 35-65 years, were used. Diabetes was defined as a fasting plasma glucose (FPG) of 126 mg/dl or higher, being on diabetes medication, and/or diabetes confirmed by a health practitioner. Results . Nine thousand nine hundred ninety-nine participants were assigned to this study. The prevalence of DM, awareness, treatment, and glycemic control of DM were 8.19, 74.97, 74.75, and 32.68, respectively. Based on the adjusted models, increased age (p < 0.01 ); obesity or overweight (p < 0.01 ); being ex-smoker (p < 0.05 ); suffering from dyslipidemia (p < 0.01 ), hypertension (p < 0.01 ), or both of them (p < 0.01 ); and positive family history in the first-degree relatives (p < 0.01 ) were strongly associated with a high risk of DM, while engagement in regular physical activity (p < 0.05 ) was a protective factor. Female gender (p < 0.01 ), being older than 55 years, positive family history in the first-degree relatives (p < 0.01 ), suffering from both hypertension and dyslipidemia (p < 0.01 ), and obesity or overweight (p < 0.005 ) were negatively associated with DM awareness. Being married and widowed (p < 0.05 and <0.05) and a high BMI (p < 0.01 ) were strong predictors of receiving treatment for DM. Six to nine years of schooling (p < 0.05 ) and suffering from hypertension (p < 0.05 ) increased the probability of DM being controlled. Conclusions . When the prevalence of DM is notable, awareness and probability of receiving treatment and controlling FPG are of particular importance. A considerable proportion of the patients were aware and on treatment, which may partly be due to improving primary health care services in Iran.